A newly invasive species may promote dissimilarity of pest populations between organic and conventional farming systems. Issue 5 (1st June 2022) - Bloom, Elias H.; Constancio, Natalie; Hauri, Kayleigh C.; Szendrei, Zsofia
Abstract: Insect taxa vary in their phenology across space creating dissimilar patterns of species abundance over time. The role of human disturbances and invasive species in these patterns of temporal dissimilarity (phenological differences) across space, however, remain largely unexplored. To dissect these patterns, we evaluated four common pests and one newly invasive species ( Contarinia nasturtii ; Swede midge) at 220 time points across 2 years on organic and conventional farms. We first summarized across time and evaluated differences in pest abundance between farm management (organic and conventional). We then used generalized additive models to describe temporal patterns of abundance, disentangling phenological differences across management systems. Last, we conducted a temporal beta diversity analysis to identify which species and management practices contribute most to dissimilarity. We found that aggregating pest abundance across time and species masked differences in pest phenology across management systems and concealed variation in pest abundance that was strongly driven by an invasive species, respectively . Overall, our results suggest that organic and conventional farms may be only superficially similar in pest abundance. Rather, by accounting for time, we demonstrate a more nuanced understanding of pest communities moving beyond abundance that may be particularly important for management of newly invasive species.